Адсорбція аденінових нуклеотидів на поверхні нанокристалічного діоксиду церію - Vlasova, N. M.; Markitan, O. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2017)
The adsorption of adenine nucleotides with different phosphate chains from aqueous solutions onto nanocrystalline ceria surface was investigated. The adsorption dependences of pH and ionic strength are interpreted in terms of surface complexation theory. The equilibrium reaction constants of the formation of outer-sphere electrostatic complexes are calculated with using basic Stern model for double electric layer.